Kritik Sastra Ekologis terhadap Novel-novel Terbaru Indonesia - Andriyani, Noni; Piliang, Wilda Srihastuty Handayani (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
Environmental literary works appear as a form of literary sensitivity to society and the environment which has specific environmental tendencies. Studies using the theory of ecological literature began in around 2008 and above with a very limited number. Therefore, the development of studies of literary works with this theory is very necessary. The creation of public opinion about the importance of protecting the environment to reduce the impact of global warming is very necessary. Later, through several novels, authors have done it. However, not all messages in the novel are clearly conveyed so that they still need ecological literary criticism to understand them. Based on this, the problem raised in this study is